The Effect Of The Outdoor Learning Method On Student Learning Motivation In Science Learning In Grade IV SD: - Isnad, Nur Ilmin; Selvi, Nurhayati; Ashari Hamzah, Rahma (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to analyze the implementation of outdoor learning methods and their impact on students' learning motivation in science learning. This method is applied through observation, questionnaires, and documentation. Data analysis was carried out using descriptive and inferential statistical tests, including normality, homogeneity, and hypothesis tests. The implementation of outdoor learning methods is considered very effective in science learning because it allows fourth grade students of SD Negeri 21 Kampung Beru, Jeneponto Regency to understand scientific concepts directly. Students' learning motivation in science learning in fourth grade of SD Negeri 21 Kampung Beru, Jeneponto Regency has increased after the implementation of outdoor learning methods. This is evidenced by the increase in students' learning motivation with the implementation of outdoor learning methods, which can be seen from the enthusiasm of students in participating in learning and their activeness in discussing learning outcomes. Based on the results of the study, it is known that the Ho hypothesis is rejected and Ha is accepted, meaning that there is an effect of the use of outdoor learning methods on students' learning motivation in science learning in fourth grade of SD Negeri 21 Kampung Beru, Jeneponto Regency. This is proven by the results of the hypothesis test with a t count of 23,000 > t table 2,086